Evaluation of the effect of antimicrobial nanoparticles on bond strength of orthodontic adhesives: A review article - Amirhossein Mirhashemi; Leila Jazi (Wolters Kluwer Medknow Publications, 2021)
Background: Antimicrobial nanoparticles (NPs) have various applications in different fields of dentistry. The purpose of incorporating NPs into orthodontic adhesives is to inhibit the cariogenic bacteria and reduce decalcifications around bonded orthodontic brackets. However, they may affect the physical and mechanical properties of adhesive such as shear bond strength (SBS). This review was done to answer the question whether the incorporation of antimicrobial NPs into orthodontic adhesives changes the SBS. Materials and Methods: An electronic search was performed with keywords such as adhesives AND nanoparticles AND orthodontics AND shear strength. After screening and applying eligibility criteria, 18 relevant studies were included. Results: The pooled data suggest that except for 10 wt% of various NPs incorporation, there is no significant difference in SBS between control conventional adhesives and experimental modified ones with tested concentrations. Conclusion: The SBS of orthodontic adhesives containing up to 5% NPs is in clinical acceptable range. However, generalizing the results to in vivo situation may be problematic and further studies are required.